ANALISIS PENGARUH PERTUMBUHAN EKONOMI, PENDAPATAN ASLI DAERAH, DAN DANA ALOKASI UMUM, PRODUK DOMESTIK REGIONAL BRUTO TERHADAP REALISASI BELANJA MODAL - Purwanto, Didik (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2015)
The purpose of this study was to analyze the significance of the effect of economic growth, local revenue and general allocation funds, GDP partially on capital expenditure at the district / city in Central Java province. This study uses census study approach at Regency / City in Central Java period 2011 – 2013. The population in this study are all Regency / City Central Java as many as 35 districts / cities are composed of 29 districts and 6 Cities. Data analysis technique used classic assumption test, multiple linear regression analysis, t test, F test and coefficient of determination. The results were obtained conclusion: The results of the analysis we concluded that PAD and DAU positive and significant impact on the allocation of capital expenditure at the district / city in Central Java province. While variable economic growth and GDP does not significantly influence the allocation of capital expenditure at the district / city in Central Java province. Determination coefficient analysis results obtained value of Adjusted R Square = 0,763 means known that the influence exerted by the economic growth, revenue, General Allocation Fund and GDP on the capex to 76,3 percent while the rest (100% - 76,3%) = 23,7 percent influenced by other factors outside variables studied. Keywords: economic growth, regional income, general allocation funds, GDP, the allocation of capital expenditure.